Amphorae and coarse ware in early Roman assemblages of the colony of Pax Iulia (Beja, Portugal): imports and local production - Conceição Lopes, Maria; Roberto de Almeida, Rui; Vaz Pinto, Inês (Rei Cretariae Romanae Fautorum Acta, 2022)
Recent excavations in the area of the forum of the Roman colony of Pax Iulia (Beja, Portugal), in the province of Lusitania, have revealed the most important architectural remains of the ancient Roman town discovered so far, albeit seriously damaged by the construction of other buildings in Late Medieval and Modern times. Apparently, they belong to the remains of three buildings that have been interpreted as a cistern and the podiums of two temples. They seem to have been built between the final Republic and the Julio-Claudian periods, their primary use occurring from the Late Republican period to the 2nd century AD. This paper presents the ceramic assemblages, mostly composed of amphorae and coarse ware, from several preserved contexts and discusses the significance of regional and imported pottery that reflect the installation and development of the colony.